Asymptomatic bacteriuria of pregnant women in a tertiary care centre - Meenakshi Totadhri; Anandhi Lakshmanan; M P Saraswathy; Manisha S Mane (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Asymptomatic bacteriuria (ASB) is commonly seen during pregnancy due to the various morphological, hormonal, and physiological changes the body undergoes. If left undiagnosed, it can lead to conditions such as pyelonephritis and preterm delivery which could culminate in causing maternal and fetal morbidity and mortality. Therefore, this study aims to determine the prevalence, risk factors, microbial profile, and antibiotic susceptibility patterns associated with ASB in a tertiary healthcare center. MATERIALS AND METHODS: A cross-sectional study was carried out where 150 urine samples were obtained from pregnant women within the gestational age of 13-36 weeks. Randomized stratified sampling was the method of sampling used. A questionnaire was also administered to them to determine potential risk factors. The samples were cultured and identified using biochemical tests. Antibiotic susceptibility tests were carried out by Kirby-Bauer disc diffusion method. Statistical analysis was carried out using Chi-square test. The graphs and tables were generated using Microsoft Excel and Word. RESULTS: Out of the 150 samples that were obtained, 8 samples had significant bacteriuria which is a prevalence of 5.33%. Escherichia coli was the most frequently isolated organism accounting to 45% of the isolates. The other organisms that were isolated were Enterococcus, Klebsiella pneumoniae, Coagulase negative staphylococcus (CONS), Candida albicans, and Group B Streptococcus which measured to 11% of the total distribution each. In the antibiotic sensitivity tests, among the gram-negative isolates, marked resistance to Ampicillin and Amoxycillin along with sensitivity to Cotrimoxazole and Nitrofurantoin. Of the gram-positive isolates, there was sensitivity to Ampicillin and Nitrofurantoin. A positive correlation was seen between the age groups of 23-27 and the prevalence of ASB. CONCLUSION: The prevalence of ASB in this study shows that ASB is not uncommon in the population. Despite the World Health Organization (WHO) guidelines and National Health Mission recommendations to make urine check-ups a routine, it not carried out, possibly due to cost implications. However, it poses a risk for severe maternal and fetal outcomes and hence, should be screened for on a regular basis. Thus, this study emphasizes the importance of screening pregnant women for ASB for promoting better maternal and fetal health.